Development of educational materials for teaching portuguese as a second language to deaf students: exploring literacy practices in higher education - Silva, Giselli Mara da; Barbosa, Eva dos Reis Araújo (The ESPecialist, 2025)
In this text, we present a project aimed at developing educational materials for teaching Portuguese as a second language to deaf students in higher education. For the design of the project and the educational materials, contributions from studies on bilingualism and bi/multilingual education (García; Woodley, 2015; Peluso; Lodi, 2023); literacy (Carvalho; Castanheira; Machado, 2023; Silva, 2010; Papen, 2023); textual genres (Bakhtin, 2006; Marcuschi, 2005); and Multimodality (Kress, 2003; Kress; van Leeuwen, 2001) are explored. In the process of material development, the teachers map out different literacy practices at the university and in other contexts, select texts, and create activities for reading, writing, and expanding lexicogrammatical resources. Subsequently, project fellows work on translating content into Brazilian Sign Language (Libras), formatting the materials, incorporating multimodal elements, and editing the videos. The final product consists of a book in Portuguese with three units, which includes links and QR Codes to videos in Libras.